Uric Acid Is Elevated in Children With Obesity and Decreases After Weight Loss - Jørgensen, Rasmus Møller; Bøttger, Bjarke; Vestergaard, Esben Thyssen; Kremke, Britta; Bahnsen, Rikke Frederiksen; Nielsen, Bent Windelborg; Bruun, Jens Meldgaard (Frontiers in Pediatrics, 2022)
Introduction: Childhood obesity is an increasing condition associated with continuous obesity into adulthood and development of comorbidities. Adult studies show an association between serum uric acid (SUA) levels and body mass index (BMI). The aim of this retro perspective exploratory study was to investigate SUA in obese children and adolescents and the effects of a subsequent weight reduction. Materials & Methods: One hundred and seventy-one children (age 4-18), with obesity (i.e. BMI-SDS of +2 or higher) were included in a multifactorial lifestyle intervention. The children participating were annually measured for anthropometrics, blood samples and DEXA-scans for up to 3 years. Eighty-nine children were included for follow-up analysis. Results: After a follow-up of 20.7 ± 9.4 months a reduction in BMI-SDS of -0.34 ± 0.53 (p < 0.01) was observed. SUA was found to be positively associated with changes in BMI-SDS. SUA levels decreased in the 65 children who lost weight during the trial, conversely, SUA increased in the 23 children who gained weight during the trial (p < 0.01 between groups). Conclusion: SUA was found to correlate with measures of obesity and for the first time, this intervention demonstrates a positive relationship between SUA and weight reduction in children with obesity.